THE EFFECTIVENESS OF USING CROSSWORD PUZZLES IN IMPROVING MASTERY OF ARABIC VOCABULARY (AN EXPERIMENTAL STUDY IN GRADE 3 MIS KHAIRUL MUKMININ): فعالية استخدام الكلمات المتقاطعة على إتقان المفردات العربية (دراسة تجريبية في الصف الثالث بالمدرسة الابتدائية خير المؤمنين) - Fitriani, Rizki (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2023)
The title of this article is "The Effectiveness of Using Crossword Puzzles in Improving Mastery of Arabic Vocabulary (an experimental study in grade 3 MIS Khairul Mukminin)". The researcher chose this title because the use of Arabic learning facilities at MIS Khairul Mukminin still employs the manual method, namely the lecture method and only relies on the Arabic books. This causes students to find it very difficult and boring in learning Arabic, especially in mastering the Arabic vocabulary and students will easily forget what they have learned. The purpose of this study was to determine the effectiveness of the use of crossword puzzles in improving the mastery of the Arabic vocabulary in grade 3 MIS Khairul Mukminin. The research approach is an experimental research using data collection techniques in the form of Pre-test and Post-test. The population in this study was all grade 3 students of MIS Khairul Mukminin consisting of 32 students. While the sample was class IIIB students as an experimental group, and class IIIA students as a control group with a total of 16 people in each class. the T-test shows α = 0.05 and dk = 30, the results of Tcalculate > Ttable were obtained which were 6.41 > 1.70. This shows that the use of crossword puzzles is effective in improving the Arabic mastery of grade 3 students at MIS Khairul Mukminin.